Pengaruh Media Pembelajaran Di Masa Pandemik COVID 19 untuk Meningkatkan Minat Belajar Mahasiswa Universitas Malikussaleh - Vera Novalia; Fathiah Fathiah; Wheny Utariningsih (PTE FTK UIN Ar-Raniry, 2021)
The Covid-19 pandemic in Indonesia has changed various aspects of human life. one in the field of education, the entire campus must learn new methods online. To make learning easier online, learning media are needed. Learning media is a means of interaction between lecturers and students so that learning activities are more effective and efficient. The media can display information through sound, images, movement and color, both naturally and manipulated. With the media, learning objectives will be more easily achieved with the minimum of time and effort. Purpose: Thus the author seeks to determine the effect of the use of instructional media on student interest in learning in the histology course, Faculty of Medicine, University of Malikussaleh. Method: This research was a descriptive study with a cross sectional survey design. The sample in this study were all students who filled out a questionnaire at Malikussaleh University. The sampling technique used purposive sampling technique and data were obtained from primary data. Result: From the regression results, it can be seen that the learning media variable has a t-count value of 4,212, which is greater than the t-table of 1,671, with a significance of 0,000, which means less than 0.05. So it can be concluded that the learning media variable has a positive and significant effect on increasing interest in learning in medical students at UNIMAL